RNA G-quadruplex structures mediate gene regulation in bacteria - Shao, Xiaolong (2021)
Guanine (G)-rich sequences in RNA can fold into diverse RNA G-quadruplex (rG4) structures to mediate various biological functions and cellular processes in eukaryotic organisms. However, the presence, locations, and functions of rG4s in prokaryotes are still elusive. We used QUMA-1, an rG4-specific fluorescent probe, to detect rG4 structures in a wide range of bacterial species both in vitro and in live cells and found rG4 to be an abundant RNA secondary structure across those species. Subsequently, to identify bacterial rG4 sites in the transcriptome, the model Escherichia coli strain and a major human pathogen, Pseudomonas aeruginosa, were subjected to recently developed high-throughput rG4 structure sequencing (rG4-seq). In total, 168 and 161 in vitro rG4 sites were found in E. coli and P. aeruginosa, respectively. Genes carrying these rG4 sites were found to be involved in virulence, gene regulation, cell envelope synthesis, and metabolism. More importantly, biophysical assays revealed the formation of a group of rG4 sites in mRNAs (such as hemL and bswR), and they were functionally validated in cells by genetic (point mutation and lux reporter assays) and phenotypic experiments, providing substantial evidence for the formation and function of rG4s in bacteria. Overall, our study uncovers important regulatory functions of rG4s in bacterial pathogenicity and metabolic pathways and strongly suggests that rG4s exist and can be detected in a wide range of bacterial species.